Do government zoning policies improve buyer-farmer relationships? Evidence from Rwanda's coffee sector. (February 2022) - Gerard, Andrew; Lopez, Maria Claudia; Mason, Nicole M.; Bizoza, Alfred R.
Highlights: Rwanda's government implemented a zoning policy in its coffee industry. Mixed methods are used to analyze how zoning affected buyer-farmer relationships. Buyers were more likely to give farmers bonuses where zoning was well-implemented. We do not find evidence that zoning increased coffee farmer investment. Buyers believed that zoning improved their relationships with farmers. Abstract: Contract farming has the potential to both connect farmers to global markets and limit farmers' sale channel choices. In countries where contract enforcement is weak, some governments have enforced monopsony zoning systems in which farmers within a zone must sell to a specific buyer. There is variance in zoning systems' effectiveness in improving relationships between suppliers and buyers. In 2016, Rwanda implemented a zoning system aimed at reducing side-selling by coffee farmers and improving service provision to farmers by coffee mills. This paper analyzes the impacts of zoning on contracting between farmers and mills. We use data from farmer surveys from before and after the shift to zoning to estimate a difference-in-differences model analyzing the effects of zoning on second payments (i.e., bonuses) paid to farmers out of mill profits. We use the share of farmers aware of zoning at the local level as a proxy for the relative strength of zoning implementation and analyze the effect of zoning on farmers being promised or receiving second payments by coffee mills. We find that an increase in the degree of zoning implementation (proxied by the proportion of local coffee farmers that know about zoning) is associated with an increase in the probability that a farmer is promised or receives a second payment. Consistent with quantitative findings, interviews with mill managers suggest that zoning motivated mills to improve service provision. We do not find evidence that zoning increased farmer investment in their coffee plantations in the short run. However, qualitative evidence suggests that zoning reduced local trader activity and farmer side-selling, which benefited mills.